Public speaking success in 20 minutes a day / Learning Express (Organization).
Public Speaking in 20 Minutes a Day, includes : Information on the different types of speeches ; Details on how to construct a meaningful and through presentation; Advice on how to prepare visual aids that will add to your speeches ;Tips on how your appearance affects the way you are perceived ;Common errors people make when in front of a crowd; A collection of famous and revered speeches from history.